2020
DOI: 10.1371/journal.pone.0237361
|View full text |Cite
|
Sign up to set email alerts
|

Memory reconsolidation as a tool to endure encoding deficits in elderly

Abstract: Normal aging involves changes in the ability to acquire, consolidate and recall new information. It has been recently proposed that the reconsolidation process is also affected in older adults. Reconsolidation is triggered after reminder presentation, allowing memories to be modified: they can be impaired, strengthened or changed in their content. In young adults it was previously shown that the presentation of repetitive reminders induces memory strengthening one day after reactivation and the presentation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…(32) showed that memory reactivation during a nap enhances skill performance. Others studies on episodic memory reconsolidation, indicated that memory reactivation strengthens the performance of older adults when tested two or seven days later (33,34). Similar results were found using transcranial Direct Current Stimulation (35).…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…(32) showed that memory reactivation during a nap enhances skill performance. Others studies on episodic memory reconsolidation, indicated that memory reactivation strengthens the performance of older adults when tested two or seven days later (33,34). Similar results were found using transcranial Direct Current Stimulation (35).…”
Section: Introductionsupporting
confidence: 57%
“…The study of memory reactivation and stabilization at long delays in populations with memory deficits is absent. Only recent work examined memory reactivation in older adults with limited evidence (31,32,34). The current findings provide evidence that memory reactivation facilitates episodic memory stabilization and improves memory retention at long delays across the lifespan.…”
Section: Discussionmentioning
confidence: 52%
“…Other studies evaluated the possibility of enhancing human memory during reconsolidation. Those assessed the sole effect of a reactivation session and also its eventual association with re-acquisition sessions, mild stressors, or physical exercise 33 , 35 , 36 , 59 61 . Our research along with Wang’s previous work 21 , emphasizes the significance of assessing the timing for associating behavioral events with reactivation sessions to enhance memory and persistence.…”
Section: Discussionmentioning
confidence: 99%
“…For example, regaining independence in performing activities of daily living involves learning processes (Bayona et al, 2005). Importantly, older adults have been shown to benefit from reconsolidation (Corbin, 2017;Tassone et al, 2020) despite the known declines in consolidation related to healthy aging (Brown et al, 2009;Wilson et al, 2012;Fogel et al, 2014;Roig et al, 2014). However, one study found that reconsolidation was impaired in older adults with stroke relative to age-matched subjects without stroke (Censor et al, 2016), while other research has found that individuals with stroke, but not age-matched healthy controls, benefit from sleep-based consolidation of a motor task Boyd, 2008, 2009).…”
Section: Consolidation and Reconsolidation During Rehabilitationmentioning
confidence: 99%